ANALYSIS OF EFFECT PRICE AND QUALITY ON BRAND IMAGE AND ITS IMPLICATION ON PURCHASE DECISION MODENA GAS COOKTOP (CASE STUDY ON GRAND GALAXY CITY RESIDENCE BEKASI) - Nahra Putra, Muhammad Thariq; Nurmahdi, Adi (Dinasti International Journal of Digital Business Management, 2020)
This study aims to determine the effect of price and quality on brand image and its implications for purchasing decisions on Modena gas cooktops. This study also examines the indirect effect of price and quality on brand image with purchasing decisions as an intervening variable. The study was conducted in the grand galaxy city residence in Bekasi. The sample in this study is consumers or at least know about Modena products with a purposive sampling method. The number of respondents who participated in this study were 100 respondents. Data collection was done through a questionnaire with a Likert scale of 1-5. The method of analysis uses path analysis using SPSS version 24.0. the results showed that price has a positive and significant effect on brand image, quality has a positive and significant effect on brand image, brand image has a positive and significant influence on purchasing decisions for Modena gas cooktop. Price has a positive and significant influence on purchasing decisions, quality has a positive and significant influence on purchasing decisions. Price and quality simultaneously have a positive and significant influence on brand image. Price and quality of brand image simultaneously have a positive and significant influence on purchasing decision